Individual responses to short-term heat acclimatisation as predictors of football performance in a hot, dry environment - Racinais, S.; Mohr, M.; Buchheit, M.; Voss, S. C.; Gaoua, N.; Grantham, J.; Nybo, L. (British Journal of Sports Medicine, 2012)
Objectives: To identify the relationship between field performance in a hot environment and individual heat acclimatisation responses in football players. Methods: Nineteen semiprofessional football players completed a match in 21°C followed by 6 days of acclimatisation in dry heat (38-43°C, 12-30% relative humidity) and a match in ~43°C. A heat-response test (30 min walk+30 min seated; 44°C) was performed at the beginning and end of the acclimatisation period. Results: The acclimatisation period increased sweat rate by 34% during a standard heat-exposure test and reduced sweat sodium concentration by 18% (both p=0.005). Plasma volume changes showed large interindividual differences (-10 to +20%). Match-running performance was impaired in hot ambient condition and demonstrated marked interindividual differences (total distance -6.0±5.8%, high-intensity running -16.4±21.5%, both p=0.002). Only haematological markers investigated during the heat-response test correlated with the ability of the player to cope with heat stress in a competitive situation; that is, changes in haematocrit between the heat-response tests were correlated to changes in total running during the game, r=-0.75; 90%CI [-0.88 to -0.51]. Conclusions: Heat acclimatisation responses and in turn, match-running performance in the heat, are highly individual. The players displaying the largest haematological adaptations were able to maintain the same activity when playing in the heat as when playing in temperate conditions. As such, team doctors might use acclimatisation indicators obtained from a heat-response test to predict the ability of individual players to cope with heat in competitive situations and individualise their preparation accordingly.